Traditional vs. Affiliation Paths Model for Science Student Success - Slovacek, Simeon; Slovacek, Simeon (Advances in Social Sciences Research Journal, 2019)
The availability of academic and personal supports is known to have a positive impact on students’ academic success, which can be particularly beneficial in the university setting. In the present study, we propose that participation in a university academic and climate support program increases students’ academic success in the Science, Technology, Engineering, and Math (STEM) fields. The aim is to answer two research questions about the dynamics of the university setting as it relates to traditional higher education versus targeted support program’s affiliation paths. Results gathered by comparing two groups (Minority Opportunities in REsearch (MORE)) programs affiliates versus non-MORE (or essentially traditional degree program paths), indicate that students affiliated with the university target program have much higher graduation rates. 88% of MORE students graduated in 6 years and 100% within 10 years, compared to non-MORE traditional students with 16% graduating in 6 years and 28% graduating within 10 years. Concerning the second research question of interest, all MORE STEM majors were compared by major while controlling for entry status of freshmen versus transfers. A two-way ANOVA showed there were no differences by major pointing to the generalizability of this type of support program.